DETERMINACIÓN NUMÉRICA DE LA RESISTENCIA AL AVANCE DE BUQUES - Valerio Mena, Lenin J. C. (1999)
The use of the Potential Theory to evaluate the Resistance to the Advance of Fishing Ships in waters calms, it is investigated, with the main objective of obtaining comparative results that allow to evaluate the acting of the theoretical method for the use in the process of the preliminary project. The simplicity and speed of the algorithm of the computer provides a valuable tool that can be used to carry out analysis of different types in ways of fine ships, including ships with bulb prow, and to obtain qualitative results at a cost very low. This way the interference of the different parts of the hull can be analyzed and the forms of the ship optimized to obtain a minimum resistance to the advance for formation of waves.